2019
DOI: 10.1101/561795
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure of the human frataxin-bound iron-sulfur cluster assembly complex provides insight into its activation mechanism

Abstract: Iron-sulfur clusters (ISC) are essential in all life forms and carry out many crucial cellular functions.The core machinery for de novo ISC biosynthesis, located in the mitochondria matrix, is a fiveprotein complex containing the cysteine desulfurase NFS1 that is activated by frataxin (FXN), scaffold protein ISCU, accessory protein ISD11, and acyl-carrier protein ACP. Deficiency in FXN leads to the loss-of-function neurodegenerative disorder Friedreich's ataxia (FRDA). Recently crystal structures depicting the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(57 citation statements)
references
References 42 publications
3
54
0
Order By: Relevance
“…Moreover, the critical amino acid residues for the interaction have been mapped [ 47 ]. Recently, it was reported the structure of a heterodecamer multiprotein complex that would be key for the biosynthesis of mitochondrial Fe-S clusters in humans containing two copies of each of NFS1, frataxin (FXN), ISCU, ISD11, and ACP [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the critical amino acid residues for the interaction have been mapped [ 47 ]. Recently, it was reported the structure of a heterodecamer multiprotein complex that would be key for the biosynthesis of mitochondrial Fe-S clusters in humans containing two copies of each of NFS1, frataxin (FXN), ISCU, ISD11, and ACP [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Also, FXN Asp124 form a salt-bridge with NFS1 Arg289, and carbonyl backbone groups from FXN residues Glu121 and Tyr123 could interact via hydrogen-bonds with NFS1 Arg119 and Arg272. It was also reported that FXN directly interacts with a second NFS1 subunit near the catalytic site via hydrophobic interaction between FXN Trp155 and NFS1 Leu386, and a hydrogen-bond between FXN Asn146 and NFS1 Ala384 [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The neural and the cardiovascular phenotypes share a common pathogenic mechanism, based on the evidence that FA is a mitochondrial disorder, affecting at the same time the nervous and the hearth tissue [ 6 , 12 , 20 , 21 , 22 , 23 ] as a consequence of the mutation of the gene encoding the mitochondrial protein Frataxin [ 24 ]. This protein plays a relevant role in modulating oxidative phosphorylation, consistent with the contribution of the mutation of the underlying gene to the disorder pathogenesis, in turn implying mitochondrial iron and sulfur accumulation within the nervous and the cardiac tissues, which results in their degeneration [ 7 , 12 , 23 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 94%